Embracing uncertainty in reconstructing early metazoan evolution - King, Nicole (Curr Biol, 2017)
The origin of metazoans, one of the major transitions in evolution, remains mysterious. While many key aspects of metazoan origins can be reconstructed by comparing living organisms within a robust phylogenetic framework, uncertainty regarding the evolutionary relationships among sponges, ctenophores and the remainder of metazoan diversity has proven to be a major barrier. Comparative morphology and some phylogenomic analyses support the view that sponges represent the sister lineage to the rest of the metazoans, while other competing phylogenomic analyses strongly support ctenophores, a phylum of carnivorous, gelatinous marine organisms, as the sister lineage. Here, we explore why different phylogenomic studies yield different answers and discuss the implications of the two alternative hypotheses for understanding the origin of metazoan multicellularity. Reconstruction of ancient evolutionary radiations, like the one that gave rise to metazoans, is devilishly difficult and will likely require broader sampling of sponge and ctenophore genomes, improved analytical strategies, and critical analyses of the phylogenetic distribution and molecular mechanisms underlying apparently conserved traits. Rather than staking out positions in favor of the ctenophore-sister or the sponge-sister hypothesis, we submit that research programs aimed at understanding the biology of the first metazoans should embrace the uncertainty surrounding early metazoan evolution in their experimental designs.